Business Motives or Educational Services? A Preliminary Study of Early Childhood Education Needs in Kendari City - Abubakar, Abubakar; Fatmawati, Titi; Nasir, Nasir (International Journal of Educational Management and Innovation, 2025)
Background. This study delves into the dichotomy between business motives and educational services in Kendari's requirements for early childhood education (ECE). The rapid growth of the education industry has led to numerous institutions offering ECE services, raising questions about the balance between profit-driven business motives and genuine educational needs. The research aims to understand dynamics by examining incentives behind establishing ECE institutions in Kendari and how they influence educational service quality and accessibility. Methods. Utilizing a mixed-methods approach, including surveys, interviews, and document analysis, the study aims to identify drivers for entrepreneurs investing in the ECE sector and their alignment with educational goals. It would explore how these motives affect comprehensive early childhood education delivery and their connection to the broader educational landscape in Kendari. Results. Findings are expected to show the equilibrium between commercial interests and educational aspirations in the ECE sector, offering insights for policymakers, educators, and stakeholders. Conclusion. By delving into the interplay between business motives and educational services, this research establishes a foundation for comprehensively exploring the ECE landscape and its implications for young learners' future development.